HUBUNGAN TINGKAT PENGETAHUAN DAN SELF EFFICACY VAKSINASI COVID-19 PADA MAHASISWA FAKULTAS KESEHATAN UNIVERSITAS NURUL JADID - Nugroho, Setiyo Adi; Istiqomah, Binti; Rohanisa, Fita (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
COVID-19 vaccine is the last weapon to reduce morbidity and prevent of death. However, in Indonesia there are many obstacles, the level of knowledge and self-efficacy is very important to note. The purpose of this study was to identify the relationship between the level of knowledge and self-efficacy in Covid-19 vaccination. A correlational study with a cross sectional approach was conducted on the student population of the Faculty of Health, Nurul Jadid University, there were 110 students who participated in this study. The independent variable is Knowledge Level while the dependent variable is Self Efficacy. The instrument in this study used a questionnaire. The results of data analysis with Spearman's rho, obtained a value of r = 0.756 and a value of p = 0.000. Based on the results of the statistical test, it was found that there was a very strong and positive patterned relationship between the level of knowledge and self-efficacy. The conclusion of this study is that there is a significant relationship between the level of knowledge and self-efficacy.